IMPLEMENTASI METODE SINGLE EXPONENTIAL SMOOTHING UNTUK PREDIKSI STOK BAHAN BAKU PROGRAM MAKAN BERGIZI GRATIS: IMPLEMENTATION OF THE SINGLE EXPONENTIAL SMOOTHING METHOD FOR FORECASTING RAW MATERIAL STOCK IN THE FREE NUTRITIOUS MEAL PROGRAM - Dewi Prima Apriliaissabella; Retno Wardhani; M. Hasan Wahyudi (LPPM Universitas Abdurrab, 2026)
The Free Nutritious Meal Program (MBG) requires effective raw material inventory management to ensure an adequate food supply. One of the problems faced by the Nutritional Fulfillment Service Unit (SPPG) Nur Amanah 10 was determining the raw material requirements for the next period because inventory planning was still carried out manually based on estimation, leading to shortages or excess inventory. This study aimed to develop a raw material inventory forecasting system using the Single Exponential Smoothing (SES) method. Historical raw material demand data were used, and alpha values ranging from 0.1 to 0.9 were evaluated to determine the optimal parameter based on the smallest Root Mean Squared Error (RMSE). The system was developed using PHP, the Laravel framework, and a MySQL database and was tested using black box testing. The results showed that 17 out of 94 raw material types met the forecasting requirements. An alpha value of 0.1 was the most frequently selected optimal parameter, while most forecasting results produced relatively low RMSE values. The system was able to display forecasting results, the optimal alpha value, RMSE values, and detailed SES calculations, thereby assisting SPPG managers in planning raw material requirements more effectively.